KEKERASAN SEKSUAL YANG TERJADI ANTAR ANAK DALAM PERSPEKTIF SISTEM PERADILAN PIDANA ANAK DI INDONESIA (STUDI PUTUSAN: PUTUSAN PENGADILAN NEGERI NOMOR 13/PID.SUSANAK/2019/PN SRG) - Lionitya Herfiana; Hery Firmansyah (Jurnal Hukum Adigama, 2021)
A child is a young human being below the age of puberty or below the legal age of majority. Children need to be taken seriously. However, as the most vulnerable and weak social beings, ironically, children are often placed in the most disadvantaged position, do not have the right to speak out, and they are often victims of violence and violations of their rights. We can also see from various mass media that almost every day various types of crimes occur, for example sexual violence. This crime can also be committed by anyone, whether children, elderly people, men or women. Sexual violence can be defined as an act or intimidation related to intimacy or sexual relations committed by the perpetrator against the victim by force, which results in the victim suffering physically, materially, mentally and psychologically. As a universal crime, this crime can be found all over the world, at every level of society, regardless of age and gender. The act of sexual violence by children that occurs is a problem that needs special attention by the government because it is related to the morality of the nation's generations. In this case the court which is the agency or institution that handles legal matters needs to pay attention to cases related to children, especially sexual crimes. Courts need to provide the most appropriate sanctions on children who commit criminal acts, especially sexual violence so that the perpetrators are deterred.